Exploring the molecular level interaction of Xenoestrogen phthalate plasticisers with oestrogen receptor alpha (ERα) Y537S mutant. Issue 17 (22nd November 2022) - Raha, Fahmida Khanam; Hasan, Jahid; Ali, Ackas; Fakayode, Sayo O.; Halim, Mohammad A.
ABSTRACT: Phthalates are Endocrine Disrupting plasticisers (EDCs) which can compete with natural oestrogens and modify ER's biological responses. Gene expression experiments show oestrogenic and anti-oestrogenic effects of phthalates on ERα. Phthalates have been examined for anti-oestrogenic activities against a somatic mutation of ERα, Y537S, a key mutation in ER-positive breast cancer cells. Here, we examined the binding affinity, dynamic characteristics, and quantitative structure–activity connection of certain phthalates against a constitutively active somatic mutant ERα (Y537S). We compared their molecular dynamic and energetic properties with 4-Hydroxytamoxifen (4OHT) and Thioridazine. Using Molecular Dynamics Simulation and protein structure analyses, we found that ligand binding altered the hydrophobic core and phthalates affected the secondary structure of Y537S ERα but did not affect H11, H11–H12 loop, H12, or antiestrogen-resistant areas. The phthalate stabilised the mutant ERα agonist structure. Compared to the Apo conformation, the Phthalate-bound H11–H12 loop and H12 displayed less fluctuation and movement. This research shows that phthalates can impair ER+ positive breast cancer cells by maintaining the agonist conformation rather than demonstrating anti-oestrogenic actions. Principal component analysis (PCA) and partial-least-square (PLS) regression were used to further understand phthalate ligands' binding to ER LBD. PLS model accurately predicted phthalates ligands' binding energy (>94%).